Temporal Variability of Fluvial Sand Composition: An Annual Time Series From Four Rivers in SW Germany - Stutenbecker, L.; Scheuvens, D.; Hinderer, M.; Hornung, J.; Petschick, R.; Raila, N.; Schwind, E. (Journal of geophysical research. Earth surface, 2023)
The sampling of fluvial sediment is subject to many sources of uncertainty, for example, time and location, and the number of samples collected. It is nevertheless commonly assumed that a sample taken at one time and location provides a somewhat averaged compositional signal. Any spatial or temporal variability of this signal is often neglected. This study investigates how the composition of bed load sand changes over an observation period of 1 year in four river basins with differing bedrock geology in southwestern Germany. Up to 12 bulk sediment samples were taken at the same locations using the same approach and analyzed for their granulometry and geochemistry. The results indicate that (a) different grain sizes yield different compositions due to source rock composition and hydraulic sorting effects, (b) bulk sediment composition changes temporally due to changing grain‐size distribution, and (c) compared to the bulk sample, the composition of narrow grain sizes is temporally more stable but nevertheless has an average variability of 15%. Because heavy mineral‐bound elements such as Zr have the highest variability, we relate a major component of compositional variability to temporally varying heavy mineral concentrations in response to hydrodynamic processes. Mixing modeling demonstrates that the fluvial sand faithfully reflects its catchment geology and that the sediment sources do not change substantially during the observation period, even during a flooding event. We conclude (a) that the causes for compositional variability may be disentangled using chemical and granulometric time series data and (b) that narrow grain sizes yield representative source rock contributions. Plain Language Summary Sediment transported by rivers is generated by the erosion of the rocks present within the river catchment area. The composition of this sediment is controlled by various processes in the catchment, for example, climate, rock type, weathering, and flow strength. Geoscientists can use modern river sediment to understand how these processes impact sediment composition, and then apply this information to the geologic time. Sampling the river sediment is often the first step in such studies, but few studies consider the sources of uncertainty during sampling, for example, time and location of sampling, and number of collected samples. For this study, we returned to the same river location during the course of 1 year to take bulk sediment samples and analyzed how variable the size of sediment grains and the sediment chemistry are. We discovered that different grain sizes yield different chemical compositions, and this is caused by differences in rock type and hydraulic processes. Because the proportion of different grain sizes in the bulk sediment changes over the year due to water flow conditions, the chemistry of the bulk sediment sample changes over the year. We provide some quantitative estimates for this variability that should be considered in similar studies. Key Points Bed load sand from 4 rivers was sampled monthly over the course of 1 year to analyze the temporal compositional variability Composition is grain‐size‐dependent, and narrow grain‐size fractions show less variability than bulk sediment samples Composition changes during the year, and this is related to changing grain‐size distributions rather than changing sediment sources